PENGUJIAN KOMPOSISI PUPUK BOKASHI DAN FERINSA PADA TANAMAN PADI GOGO BERAS MERAH (Oryza nivara L.) VARIETAS INPAGO 7 - Erwin ' Saputra; Gunawan ' Tabrani; Elza ' Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to increase the production of upland red rice plants with organic fertilizer of bokashi and ferinsa.This research was conducted at the experimental farm of the Agriculture Faculty, University of Riau started in May to August 2015. The experiment using a completely randomized design 7 treatments and 3 replications and. The treatments in this research are b0 = without fertilizer, b1 =60 g Bokashi and 10% ferinsa, b2 = 60 g Bokashi and 20% Ferinsa, b3 = 60 g Bokashi and 30% Ferinsa, b4 = 120 g Bokashi and 10% Ferinsa, b5 = 120 g Bokashi and 20% Ferinsa (%), b6 = 120 g Bokashi and 30% Ferinsa. Parameters observed are hight of plant, the maximum number of tillers, the number of productive tillers, the appearance ofpanicle, panicle length, number of grain per panicle, percentage of of grain pithy and dry weight of grain. The results of observation data were further analyze by Duncan new multiple range test at 5%level.The results showed thatthe composition of bokashi and ferinsa gave effect on hight of plant, the maximum number of tillers, the number of productive tillers, the appearance of panicle, panicle length, number of grain per panicle, percentage of grain pithy and dry weight of grain. Bokashi fertilizer composition 120 g and ferinsa 30 % is the best treatment to increase the production of upland red rice plants compared to other treatment. Keywords : Bokashi fertilizer, ferinsa, red rice plants.